Lung ultrasound findings in asymptomatic healthy children with asthma. Issue 10 (12th July 2022) - Marzook, Noah; Gagnon, Francois; Deragon, Alexandre; Zielinski, David; Shapiro, Adam J.; Lands, Larry C.; Dubrovsky, Alexander S.
Abstract: Background: Lung ultrasound (LUS) has been shown to be an effective tool to rapidly diagnose certain causes of pediatric respiratory distress. However, very little is known about LUS findings in pediatric asthma. Objectives: The primary objective of this study was to characterize LUS findings in a cohort of pediatric patients with a definitive diagnosis of asthma, outside of an asthma exacerbation. Methods: Eligible patients, aged 6−17 years old and diagnosed with asthma, underwent LUS during an outpatient visit. LUS was conducted using a six‐zone scanning protocol. Presence of a LUS artifact was defined by one or more of the following: ≥3 B‐lines per intercostal space, pulmonary consolidation, and/or pleural abnormality. Images were interpreted by an expert sonographer blinded to patient clinical characteristics. Results: Fifty‐two patients were included. 10/52 (19.2%) patients demonstrated the presence of LUS artifacts: 8 with ≥3 B‐lines, 1 with consolidation >1 cm, and 7 with subpleural consolidations <1 cm, 1 with a pleural line abnormality. Artifacts were seen in the right anterior and lateral zones in 60% of participants and were limited to 1−2 intercostal space(s) within one lung zone in all participants. No association was found between presence of LUS artifacts and asthma control or severity. Conclusion: To our knowledge, this is the first report of LUS findings in outpatient pediatric asthma. LUS artifacts in asthmatic children can be seen outside of acute exacerbations. Such baseline findings need to be taken into consideration when using LUS for the acute evaluation of a pediatric patient with asthma.